Effect of Toothbrushing Application for Kids on Dental Plaque Removal and Interest in Toothbrushing of Preschool Children - Chae-Ha Hwang; Hyeon-Ju Song; Min-Ji Jung; Yeon-Jae Choi; Young Sun Hwang (치위생과학회지, 2023)
Background: Dental caries in preschool children can cause early loss of teeth, reduced masticatory function, malocclusion, and speech disorders, making oral care for preschool children essential. However, because children have a poor ability to perform oral hygiene by themselves, educational tools that help establish correct oral health behaviors are required. This study evaluated the effect of toothbrushing application for kids on dental plaque removal and toothbrushing interest in preschool children.Methods: Seven 5-year-old children enrolled in a daycare center participated in the evaluation, and the same children participated in the experiment twice a week. The Pokémon Smile application (App) was used as an auxiliary application for tooth brushing, and the degree of dental plaque removal on the tooth surface was evaluated by quantitative light-induced fluorescence-digital imaging. After the experiment, children’s toothbrushing preferences were investigated through interviews. Results: The levels of AREA R30 and AREA R70 measured after the children’s toothbrushing as usual decreased compared to those before toothbrushing; however, the change was not significant. The levels of AREA R30 and AREA R70 measured after using the Pokémon Smile App were significantly reduced compared to those before toothbrushing. Children’s interest in brushing their teeth increased by 28.59% after using the Pokémon Smile App. Conclusion: The toothbrushing application for kids effectively removes dental plaque by helping preschool children brush their teeth. It also increased preschool children’s interest in tooth brushing. Therefore, an oral health education application would be useful for children who need to develop correct oral care methods and habits.